2015
DOI: 10.3889/oamjms.2015.056
|View full text |Cite
|
Sign up to set email alerts
|

Beetroot-Carrot Juice Intake either Alone or in Combination with Antileukemic Drug 'Chlorambucil' As A Potential Treatment for Chronic Lymphocytic Leukemia

Abstract: Chronic lymphocytic leukemia (CLL) is one of the chronic lymphoproliferative disorders (lymphoid neoplasms). It is characterized by a progressive accumulation of functionally incompetent lymphocytes. Patients with leukemia often seek unconventional treatments not prescribed by hematologist in order to improve their cancer treatment outcome or to manage symptoms. In the present report, a 76-year-old patient was diagnosed with B-cell chronic lymphocytic leukemia (B-CLL). Beetroot-carrot juice is used as a comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Only an isolated case report on an elderly patient diagnosed with chronic lymphocytic leukemia and her clinical experiences with beetroot juice was published. The patient who refused chlorambucil after a recurrence of disease, was started with beetroot-carrot juice [ 77 ]. In the clinical follow-up duration, administration of beetroot-carrot juice alone induced a reduction in lymphocyte and peripheral blood leukocytes count by 14.7% and 43.13%, respectively with a concurrent decrease in the uric acid level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only an isolated case report on an elderly patient diagnosed with chronic lymphocytic leukemia and her clinical experiences with beetroot juice was published. The patient who refused chlorambucil after a recurrence of disease, was started with beetroot-carrot juice [ 77 ]. In the clinical follow-up duration, administration of beetroot-carrot juice alone induced a reduction in lymphocyte and peripheral blood leukocytes count by 14.7% and 43.13%, respectively with a concurrent decrease in the uric acid level.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, her condition was reversed when beetroot-carrot juice was reintroduced. This observation provides single but limited evidence for the effectiveness of the beetroot-carrot juice in eliminating malignant leukemic cells [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that beet juice may increase the anticancer effect of doxorubicin [9]. A case report suggested that the combination of chlorambucil with beet juice and carrot juice is beneficial in a B-CLL leukemia patient [32]. Finally, the consumption of large amounts of carrot juice and beet juice was shown to reduce the anticancer effects of cisplatin [33].…”
Section: Beet Juice Carrot Juicementioning
confidence: 99%
“…This probably attributed to betalains for its ability to reduce the mRNA level of COX‐2 and IL‐8. For chronic lymphocytic leukemia (CLL) patients, it has begun to be gradually accepted that the application of beetroot–carrot juice provided a successful treatment for the complementary or alternative therapy combined with chlorambucil, a conventional leukemic treatment drug (Shakib et al., 2015 ). This effect was proved by the decrease of the number of leukocytes, lymphocytes in peripheral blood and improve the relevant biochemical parameters.…”
Section: Biological Activitymentioning
confidence: 99%